The Impact of Emoji Use on Perception Differences in Online Conversations among Teenagers - Salsabila, Naisa Syahra; Rahma, Annisa; Agustin, Astri; Nanda, Dea; Rahman, Aam Ali (LITERA : Jurnal Bahasa Dan Sastra, 2025)
In the digital era, teenagers now communicate more often through online platforms. One of the current growing phenomena is the use of emojis. Emojis act as nonverbal elements that can influence various aspects of the communication process. Emojis can affect the intonation and clarity of meaning of the message to be conveyed, without elements of sound or facial expressions, written messages are often ambiguous or even misperceived. Emojis are effective in reducing communication confusion by providing additional visual cues about the sender's intentions and emotions. This study aims to understand the phenomenon of emojis used in online conversations in depth and their impact on differences in perception among teenagers. This study utilized a qualitative research design with a case study approach among teenagers. The study's results showed a significant influence on differences in perception and perspective in the use of emojis among teenagers. So, it is important to understand the context and meaning of emojis to reduce the risk of misunderstandings and differences in perception in online communication in this digital era. Through a better understanding of the use of emojis, it is hoped that a more effective and harmonious communication environment can be created.